2021
DOI: 10.3390/ijerph18031230
|View full text |Cite
|
Sign up to set email alerts
|

Access to Healthcare Following Serious Injury: Perspectives of Allied Health Professionals in Urban and Regional Settings

Abstract: Barriers to accessing healthcare exist following serious injury. These issues are not well understood and may have dire consequences for healthcare utilisation and patients’ long-term recovery. The aim of this qualitative study was to explore factors perceived by allied health professionals to affect access to healthcare beyond hospital discharge for people with serious injuries in urban and regional Victoria, Australia. Twenty-five semi-structured interviews were conducted with community-based allied health p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
(68 reference statements)
1
17
0
Order By: Relevance
“…The interplay of health literacy and access themes developed in this study is similar in complexity and interconnectedness to those identified in other research studies among rural healthcare providers [ 11 , 17 , 43 , 51 ]. Any potential improvement, service redesign, and policy changes aimed at reducing PPHs will require consideration of the views of both patient and provider.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The interplay of health literacy and access themes developed in this study is similar in complexity and interconnectedness to those identified in other research studies among rural healthcare providers [ 11 , 17 , 43 , 51 ]. Any potential improvement, service redesign, and policy changes aimed at reducing PPHs will require consideration of the views of both patient and provider.…”
Section: Discussionsupporting
confidence: 67%
“…Deficiencies in other dimensions of ‘access to care’ (viz. geographic accessibility, organisational accommodation, affordability, and acceptability) were considered to increase the risk of PPHs in rural populations in this and other studies [ 50 , 51 ]. The disparate healthcare needs of rural populations may be better served by focussing improvements on the ‘non-supply’ dimensions of healthcare access.…”
Section: Discussionmentioning
confidence: 99%
“…2 , Fig. 3 ) ( Keeves et al, 2021 ). Although the urban centralisation of medical specialist services is necessary ( Lawrence & Fudge, 2009 ), it has the potential to be problematic for suburban people with complex rehabilitation needs, who require regular and timely access to these services ( Solovieva & Walls, 2014 ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous telehealth research, both pre-dating and published since the advent of the pandemic, has typically focused on the experience of healthcare workers who deliver telehealth to a range of patient groups. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 Where the client experience has been explored, this has usually been in the context of healthcare delivery to rural and remote areas. 8 , 11 This paper provides a useful addition to the telehealth literature, particularly in the area of hand therapy.…”
Section: Discussionmentioning
confidence: 99%